Biocompatible gold nanorods one-step surface functionalization, highly colloidal stability, and low cytotoxicity - Liu, Kang (Langmuir : the ACS journal of surfaces and colloids, 2015)
The conjugation of gold nanorods (AuNRs) with polyethylene glycol (PEG) is one of the most effective ways to reduce their cytotoxicity arising from the cetyltrimethylammonium bromide (CTAB) and silver ions used in their synthesis. However, typical PEGylation occurs only at the tips of the AuNRs, producing partially modified AuNRs. To address this issue, we have developed a novel, facile, one-step surface functionalization method that involves the use of Tween 20 to stabilize AuNRs, bis(p-sulfonatophenyl)phenylphosphine (BSPP) to activate the AuNR surface for the subsequent PEGylation, and NaCl to etch silver from the AuNRs. This method allows for the complete removal of the surface-bound CTAB and the most active surface silver from the AuNRs. The produced AuNRs showed far lower toxicity than other methods to PEGylate AuNRs, with no apparent toxicity when their concentration is lower than 5 μg/mL. Even at a high concentration of 80 μg/mL, their cell viability is still four times higher than that of the tip-modified AuNRs